A Case of Definitive Therapy for Localised Prostate Cancer: Report of a Urological Nightmare - Andreas Sommerhuber; Verena Traxlmayr; Wolfgang Loidl (Advances in Urology)
Radical prostatectomy, external beam radiotherapy and permanent brachytherapy are the most common treatment options for nonmetastatic localised adenocarcinoma of the prostate (PCa). Accurate pretherapeutic clinical staging is difficult, the number of positive cores after biopsy does not imperatively represent the extension of the cancer. Furthermore postoperative upgrading in Gleason score is frequently observed. Even in a localised setting a certain amount of patients with organ-confined PCa will develop biochemical progression. In case of a rise in PSA level after radiation the majority of patients will receive androgen deprivation therapy what must be considered as palliative. If local or systemic progressive disease is associated with evolving neuroendocrine differentiation hormonal manipulation is increasingly ineffective; radiotherapy and systemic chemotherapy with a platinum agent and etoposide are recommended. In case of local progression complications such as pelvic pain, gross haematuria, infravesical obstruction and rectal invasion with obstruction and consecutive ileus can possibly occur. In this situation palliative radical surgery is a therapy option especially in the absence of distant metastases. A case with local and later systemic progression after permanent brachytherapy is presented here.